An improved draft genome sequence of hybrid Populus alba × Populus glandulosa - Huang, Xiong; Chen, Song; Peng, Xiaopeng; Bae, Eun-Kyung; Dai, Xinren; Liu, Guiming; Qu, Guanzheng; Ko, Jae-Heung; Lee, Hyoshin; Chen, Su; Li, Quanzi; Lu, Mengzhu (Journal of forestry research, 2021)
Populus alba × P. glandulosa clone 84 K, derived from South Korea, is widely cultivated in China and used as a model in the molecular research of woody plants because of high gene transformation efficiency. Here, we combined 63-fold coverage Illumina short reads and 126-fold coverage PacBio long reads to assemble the genome. Due to the high heterozygosity level at 2.1% estimated by k -mer analysis, we exploited TrioCanu for genome assembly. The PacBio clean subreads of P. alba × P. glandulosa were separated into two parts according to the similarities, compared with the parental genomes of P. alba and P. glandulosa . The two parts of the subreads were assembled to two sets of subgenomes comprising subgenome A (405.31 Mb, from P. alba ) and subgenome G (376.05 Mb, from P. glandulosa ) with the contig N50 size of 5.43 Mb and 2.15 Mb, respectively. A high-quality P. alba × P. glandulosa genome assembly was obtained. The genome size was 781.36 Mb with the contig N50 size of 3.66 Mb and the longest contig was 19.47 Mb. In addition, a total of 176.95 Mb (43.7%), 152.37 Mb (40.5%) of repetitive elements were identified and a total of 38,701 and 38,449 protein-coding genes were predicted in subgenomes A and G, respectively. For functional annotation, 96.98% of subgenome A and 96.96% of subgenome G genes were annotated with public databases. This de novo assembled genome will facilitate systematic and comprehensive study, such as multi-omics analysis, in the model tree P. alba × P. glandulosa .